Revisiting the nomenclature and taxonomy of the Malagasy Kalanchoe uniflora (K. subg. Alatae; Crassulaceae subfam. Kalanchooideae), which has Kitchingia uniflora as its basionym, and its homotypic and heterotypic synonyms - Smith, Gideon F. (Phytotaxa, 2024)
The Malagasy Kalanchoe uniflora (Crassulaceae subfam. Kalanchooideae) was at first described as a species of Kitchingia, but soon thereafter transferred to Kalanchoe. The taxonomy and nomenclature of Kalanchoe uniflora are reviewed and discussed in a historical context. An amplified description and illustrations are provided for the species. The typification of the name Kitchingia uniflora, basionym of Kalanchoe uniflora, is corrected, and the typification of the name Kalanchoe ambrensis, a heterotypic synonym of Kalanchoe uniflora, is dealt with.